A cautionary tale on polygyny, conflict and gender inequality - Tim Krieger; Laura Renner (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2018)
Kanazawa (J of Politics, 2009) claims that polygyny may be the "first law of intergroup conflict (civil wars)". Gleditsch et al. (J of Politics, 2011) reject this claim by showing that the effect of polygyny on civil war onset disappears once misogyny is controlled for. Our paper recapitulates this theoretical and empirical debate. We explore further theoretical arguments and replicate and extend the empirical analysis of Gleditsch et al. Our analysis is based on data from 123 countries from the period 1981-2011. Our results show that there is some truth to the empirical claims of both articles: Both polygyny and gender inequality matter in explaining the onset of internal conflicts. However, the results are sensitive to regional sample splits as well as the choice of the dimensions of gender inequality. The most pronounced effects can be found in a subsample of 40 African countries.
Keywords: D74; J12; J16; 330; Polygyny; Misogyny; Gender Inequality; Intrastate Conflict; Civil War